INSTITUTIONAL WEAKENING AND THE REVERSAL OF CONSERVATION EFFECTIVENESS: evidence from deforestation dynamics in the Brazilian Amazon - dos Santos Flores, Willian; Gonçalves da Silva, Jonathan; Bonfim de Almeida, Roselaine; Vinícios Carvalho, Leandro (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2026)
Between 2015 and 2023, the Brazilian Legal Amazon lost an averaging roughly 9,000 km² of forest annually, a reversal of previous conservation gains. Using municipality-level panel data with fixed effects, this study provides the assessment of how economic incentives and conservation policies interact under conditions of institutional weakening. Three main results were found. First, cattle prices and rural credit volumes remain positively associated with deforestation, confirming livestock as the primary land conversion driver. Second, soybean prices exhibit a negative coefficient, consistent with the Soy Moratorium’s effectiveness in decoupling agricultural profits from forest conversion. Third, and most concerning, Permanent Protected Areas established before 2015 show a positive correlation with deforestation in the post-2015 period, suggesting leakage effects when surrounding governance deteriorates. Environmental agency staffing reduces deforestation only in restricted specifications, losing significance when institutional and land-cover controls are included. These findings demonstrate that conservation effectiveness is not an intrinsic property of protected areas but an emergent outcome of institutional resilience. Given the Amazon’s centrality to global climate regulation, weakening environmental governance in tropical forest regions may undermine international climate mitigation efforts.